Modification of the refractive index response of long period gratings using thin film overlays. - Ishaq Imran, M; Quintela, Antonio; James, Stephen W.; Ashwell, Geoffrey J.; Tatam, Ralph P. (Elsevier Science B.V., Amsterdam., 2005)
The response of a fibre optic long period grating (LPG) to the surrounding refractive index is shown to be modified by the deposition of a thin film of thickness of order 100 nm onto the cladding. The LPG becomes sensitive to surrounding refractive indices greater than that of silica, and exhibits an enhanced sensitivity to external refractive indices lower than that of silica.
Keywords: Long period grating; Refractive index; Transmission spectrum; Langmuir-Blodgett